Tropical Diseases, Travel Medicine and Vaccines - Riddle, Mark
Tropical Diseases, Travel Medicine and Vaccines is an open access journal that considers basic, translational and applied research, as well as reviews and commentary, related to the prevention and management of healthcare and diseases in international travelers. Given the changes in demographic trends of travelers globally, as well as the epidemiological transitions which many countries are experiencing, the journal considers non-infectious problems including chronic disease among target populations of interest as well as infectious diseases.